2018
DOI: 10.1002/jcb.26562
|View full text |Cite
|
Sign up to set email alerts
|

NES1/KLK10 promotes trastuzumab resistance via activation of PI3K/AKT signaling pathway in gastric cancer

Abstract: Trastuzumab, a humanized antibody targeting human epidermal growth factor receptor 2 (HER2), exhibits remarkable therapeutic efficacy against HER2-positive gastric cancer. Acquired resistance to trastuzumab remains a barrier to patient survival and the mechanisms underlying this are still not well understood. The normal epithelial cell-specific-1 (NES1) gene, also named as KLK10, is recognized as a potential therapeutic target for reversing trastuzumab resistance. The aim of this study was to explore the poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 28 publications
2
20
0
Order By: Relevance
“…Similarly, aberrant elevation of KLK10 promotes cell invasion and metastasis in pancreatic ductal adenocarcinoma [13]. Analogously, KLK10 elevation enhances trastuzumab resistance in gastric cancer [12]. However, KLK10 is recognized as a putative tumor suppressor in prostate cancer as the fact that KLK10 overexpression decelerates tumor proliferation and induces cell apoptosis [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, aberrant elevation of KLK10 promotes cell invasion and metastasis in pancreatic ductal adenocarcinoma [13]. Analogously, KLK10 elevation enhances trastuzumab resistance in gastric cancer [12]. However, KLK10 is recognized as a putative tumor suppressor in prostate cancer as the fact that KLK10 overexpression decelerates tumor proliferation and induces cell apoptosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…KLK10 was initially identified in 1996 as normal epithelial cell-specific 1 (NES1). Increasing evidence has confirmed the aberrant expression of KLK10 in several cancers, including pancreatic ductal adenocarcinoma, breast cancer, and gastric cancer [12,13]. However, abundant study substantiates the contradictive roles of KLK10 in the development of cancers by regulating cell growth, invasion, and apoptosis [13,14].…”
mentioning
confidence: 99%
“…Inactivation of Hippo F I G U R E 4 Overexpression of miR-10a repressed expression of YAP and its target genes. 29 Particularly, KDM4A was recently discovered to stimulate YAP transcription via recruited to the promoter of YAP gene. D, Activation of YAP promoter luciferase reporter by overexpression of KDM4A could be reversed by transfection of miR-10a mimics in 293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal activation of the PI3K/AKT pathway has been reported to be one of the important mechanisms of inducing drug resistance in tumor cells. 64,65 And further studies have showed that some chemotherapeutics would activate the PI3K/AKT pathway which resulted in acquired drug resistance. 66,67 So far, the mechanisms of the PI3K/AKT pathway have not been fully understood.…”
Section: Change Of Apoptosis and Autophagy Dysfunction Of Apoptosis Pmentioning
confidence: 99%